Mathematics
rubykluis
12

What is p in the following equation 17=p-3-3p?

+1
(1) Answers
Ludivina788

Simplifying 17 = p + -3 + -3p Reorder the terms: 17 = -3 + p + -3p Combine like terms: p + -3p = -2p 17 = -3 + -2p Solving 17 = -3 + -2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '2p' to each side of the equation. 17 + 2p = -3 + -2p + 2p Combine like terms: -2p + 2p = 0 17 + 2p = -3 + 0 17 + 2p = -3 Add '-17' to each side of the equation. 17 + -17 + 2p = -3 + -17 Combine like terms: 17 + -17 = 0 0 + 2p = -3 + -17 2p = -3 + -17 Combine like terms: -3 + -17 = -20 2p = -20 Divide each side by '2'. p = -10 Simplifying p = -10      Hope I helped Brianliest if satisfied :D

Add answer